PENINGKATAN PEMAHAMAN BUSINESS MODEL CANVAS DAN LEGALITAS USAHA BAGI WOMENPREUNER UNTUK MENDUKUNG KEBERLANJUTAN UMKM DI KOTA PANGKALPINANG - Aprilian, Rahil Imainul; Kustiawan, Elyas; Zulkarnain, Ariandi A; Yanto, Yanto; Putra , Agung Rizki (Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving regional economic growth, creating employment opportunities, and improving community welfare. In Indonesia, the majority of MSME actors are women (womenpreneurs) who are actively involved in various local economic sectors. However, many of these womenpreneurs still face challenges in formulating systematic business plans and fulfilling business legality requirements.This community service activity aims to enhance the understanding of female MSME actors—particularly members of the Persaudaraan Muslimah (Salimah) organization in Pangkalpinang City—in designing business models using the Business Model Canvas (BMC) approach and to increase awareness of the importance of business legality, such as obtaining a Business Identification Number (NIB). The activity was carried out through training, outreach, interactive discussions, and simulations of BMC formulation and legality registration via the Online Single Submission (OSS) system.To assess the effectiveness of the training, pre-tests and post-tests were conducted with the participants. The results showed a significant improvement in participants' understanding of the BMC concept and business legality, as well as a positive change in their attitudes and readiness to apply both to their businesses. Therefore, this activity has proven effective in encouraging womenpreneurs to develop their businesses in a more structured, formal, and sustainable manner through proper business planning and compliance with business regulations.